Addressing authorized absences: a school district’s initiative to examine prevalence and promote proactive attendance practices - Heyne, David; Verstraete, Inge; de Wit, Marije (Frontiers in Education, 2025)
BackgroundAuthorized absences often receive less attention from policymakers and researchers, despite having a similar impact to unauthorized absences. The GRIP study aimed to help a Dutch school district ‘get a grip’ on attendance by raising awareness of authorized absences and supporting improvements in attendance practices.MethodUsing an action research approach, two district-level consultants prioritized building trust with school staff, administrators, and district personnel to foster collaboration in the study. With the participation of 31 of the district’s 33 secondary schools, they accessed and analyzed absence data from the 2018/2019 academic year. A key step was standardizing absence categories across schools to gain a clearer picture of absences across the district. A launch event was held to communicate findings and start helping schools translate data insights into attendance improvement practices.ResultsAuthorized absences accounted for 85.5% of all missed class time. Sickness/medical-related absences and school-initiated absences were the most prevalent, comprising 75 and 16% of all authorized absences, respectively. There was little evidence that schools responded to authorized absences prior to the current study. Through the collaborative process that characterized the GRIP study, schools became more aware of authorized absences and received support in implementing practices to improve attendance, sparking growing interest among schools in establishing an attendance taskforce of their own.ConclusionSchools have substantial influence over authorized absences, particularly school-initiated ones, offering opportunities to reduce unnecessary absences. Six key drivers for improving school attendance emerged from the consultants’ reflections: district-wide collaboration, trust-building through non-judgmental engagement, using data to trigger urgency, empowering schools with data-driven insights, applying a tiered approach to attendance, and adopting an adaptive approach for continuous improvement. Future research should focus on refining absence registration systems and incorporating qualitative methods to better understand authorized absences and improve interventions.